Effective spatial scales for evaluating environmental determinants of population density in Yakushima macaques. Issue 2 (17th September 2014) - Agetsuma, Naoki; Koda, Ryosuke; Tsujino, Riyou; Agetsuma‐Yanagihara, Yoshimi
<x xml:space="preserve">Abstract</x> Population densities of wildlife species tend to be correlated with resource productivity of habitats. However, wildlife density has been greatly modified by increasing human influences. For effective conservation, we must first identify the significant factors that affect wildlife density, and then determine the extent of the areas in which the factors should be managed. Here, we propose a protocol that accomplishes these two tasks. The main threats to wildlife are thought to be habitat alteration and hunting, with increases in alien carnivores being a concern that has arisen recently. Here, we examined the effect of these anthropogenic disturbances, as well as natural factors, on the local density of Yakushima macaques (Macaca fuscata yakui). We surveyed macaque densities at 30 sites across their habitat using data from 403 automatic cameras. We quantified the effect of natural vegetation (broad‐leaved forest, mixed coniferous/broad‐leaved forest, etc.), altered vegetation (forestry area and agricultural land), hunting pressure, and density of feral domestic dogs (Canis familiaris). The effect of each vegetation type was analyzed at numerous spatial scales (between 150 and 3, 600‐m radii from the camera locations) to determine the best scale for explaining macaque density (effective spatial scale). A model‐selection procedure (generalized linear mixed model) was used to detect significant factors affecting macaque density. We detected that the most effective spatial scale was 400 m in radius, a scale that corresponded to group range size of the macaques. At this scale, the amount of broad‐leaved forest was selected as a positive factor, whereas mixed forest and forestry area were selected as negative factors for macaque density. This study demonstrated the importance of the simultaneous evaluation of all possible factors of wildlife population density at the appropriate spatial scale. Am. J. Primatol. 77:152–161, 2015. © 2014 Wiley Periodicals, Inc.